2020
DOI: 10.4038/jas.v15i1.8673
|View full text |Cite
|
Sign up to set email alerts
|

Centellaasiatica Morphotypes Differ Genetically as well as Macronutrients Content, Total Phenolic Content and Chemical Fingerprints of Leaves

Abstract: Purpose: Centellaassiatica is an aromatic herb commonly grown in humid areas of tropical Asia. It has widely been used as a leafy vegetable and for medicinal preparations. Its medicinal and dilatory values have created a high demand for fresh consumption and value added products. Assessing morphological, biochemical and genetic diversity of existing germplasm is the essential fi rst step in cultivation and breeding eff orts. Research Method:We analyzed leaf morphological characters, macro nutrient contents, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Wide chemotypic variations in triterpenoids were found in CA planted in different growing regions, altitudes and localities ( Long et al, 2012 ; Singh et al, 2014 ; Srivastava et al, 2014 ). Genotypic and phenotypic variability have been associated with differences in phytochemicals content of CA including macronutrients, micronutrients, phenolics, flavonoids, tannin, anthocyanin, carotenoids and ascorbic acid ( Thomas et al, 2010 ; Singh et al, 2014 ; Lal et al, 2017 ; Chandrasekara et al, 2020 ). Other than geographical and genotypical influences, the phytochemical compositions of CA also vary due to seasonal variations associated with the cultivation and harvesting procedures, light conditions, as well as the drying conditions post-harvesting ( Maulidiani et al, 2012 ; Rahajanirina et al, 2012 ; Alqahtani et al, 2015 ; Plengmuankhae and Tantitadapitak, 2015 ).…”
Section: Centella Asiatica (L) Urb (Ca): the Medicinal Plantmentioning
confidence: 99%
“…Wide chemotypic variations in triterpenoids were found in CA planted in different growing regions, altitudes and localities ( Long et al, 2012 ; Singh et al, 2014 ; Srivastava et al, 2014 ). Genotypic and phenotypic variability have been associated with differences in phytochemicals content of CA including macronutrients, micronutrients, phenolics, flavonoids, tannin, anthocyanin, carotenoids and ascorbic acid ( Thomas et al, 2010 ; Singh et al, 2014 ; Lal et al, 2017 ; Chandrasekara et al, 2020 ). Other than geographical and genotypical influences, the phytochemical compositions of CA also vary due to seasonal variations associated with the cultivation and harvesting procedures, light conditions, as well as the drying conditions post-harvesting ( Maulidiani et al, 2012 ; Rahajanirina et al, 2012 ; Alqahtani et al, 2015 ; Plengmuankhae and Tantitadapitak, 2015 ).…”
Section: Centella Asiatica (L) Urb (Ca): the Medicinal Plantmentioning
confidence: 99%
“…Cluster analysis based on morphologies and agronomic characteristics was studied in various plant species, such as pigeon pea, rice and soybean [20][21][22]. In Asiatic pennywort, Chandrasekara et al [17] was clustered the 14 morphologies of 5 morphotypes of Asiatic pennywort in Sri Lanka, the results revealed that 2 differed clusters were classified. Ravi et al [23] identified the variability of 39 accessions of Asiatic pennywort in India based on 14 morphological traits, the results shown wide variability.…”
Section: Cluster Analysis and Variability Of Morphology And Agronomic Characteristic Of Asiatic Pennywort In Thailandmentioning
confidence: 99%
“…According with, Prasad et al [11] reported that the variability of Asiatic pennywort germplasm collected from different part of India shown differed biomass accumulation and madecassoside and asiatic acid content. While, Chandrasekara et al [17] revealed that germplasm evaluation of Asiatic pennywort by using morphological, biochemical and genetic diversity is the essential 1 st step in cultivation and breeding efforts. Therefore, the objective of this study aimed to collected and identified the diversity of Asiatic pennywort in Thailand by using morphological and agronomical characteristic data.…”
Section: Introductionmentioning
confidence: 99%